2020
DOI: 10.1128/mbio.00180-20
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Mediators Are Effective Biomarkers for Predicting Adverse Outcomes in Clostridioides difficile Infection

Abstract: Clostridioides difficile infection (CDI) can result in severe disease and death, with no accurate models that allow for early prediction of adverse outcomes. To address this need, we sought to develop serum-based biomarker models to predict CDI outcomes. We prospectively collected sera ≤48 h after diagnosis of CDI in two cohorts. Biomarkers were measured with a custom multiplex bead array assay. Patients were classified using IDSA severity criteria and the development of disease-related complications (DRCs), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
18
1
Order By: Relevance
“…However, we found that there was no difference in cecum and colon scores between clindamycin- and PEG-treated mice that were challenged with C. difficile at 4 days postchallenge ( Fig. 3D ), the time point typically examined in C. difficile 630-challenged mice ( 28 ). We also looked at 6 days postchallenge because that was when there was a large difference in C. difficile density between PEG- and clindamycin-treated mice ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…However, we found that there was no difference in cecum and colon scores between clindamycin- and PEG-treated mice that were challenged with C. difficile at 4 days postchallenge ( Fig. 3D ), the time point typically examined in C. difficile 630-challenged mice ( 28 ). We also looked at 6 days postchallenge because that was when there was a large difference in C. difficile density between PEG- and clindamycin-treated mice ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…However, we found there was no difference in cecum and colon scores between clindamycin and PEG-treated mice that were challenged with C. difficile at 4 days post-challenge (Fig. 3D), the time point typically examined in C. difficile challenged mice (28). We also looked at 6 days post-challenge because that was when there was a large difference in C. difficile density between PEG-and clindamycin-treated mice (Fig.…”
Section: -Day Laxative Treatment Differentially Disrupted the Fecal Microbiota Compared To Clindamycin Treatment Since Osmotic Laxatives mentioning
confidence: 89%
“…The AuROCs of these models in predicting attributable complications were 0.874 and 0.84, respectively. 84 …”
Section: Microbiologic Factors Associated With CDI Outcomesmentioning
confidence: 99%